Geomagnetic Storms and their Influence on the Human Brain Functional State. - Babayev, Elchin S.; Allahverdiyeva, Aysel A. (Revista CENIC Ciencias Biológicas)
An investigation of the influence of geomagnetic storms of various intensities on healthy adults' human brain activity and its functional state was conducted. Results of electroencephalogram (EEG) investigations were used as the most objective method reflecting functional state of the human brain. Studies on the influence of geomagnetic storms on the human brain functional state of healthy adult women patients (permanent group) in states of relaxation, photo-stimulation and hyper-ventilation have revealed a negative influence of severe geomagnetic storms on functional state of the human brain. As a rule, during periods of strong geomagnetic disturbances, indisposition, weakness and presence of indistinct localized headaches were recorded for majority of patients. Complex of nonspecific shifts on EEG reflects disorganization of functional activity of cortex of large hemispheres of the human brain at geomagnetically disturbed days, which is likely connected with dysfunction of integrative subcortical systems, with disbalance of its ascending synchronizing and desynchronizing influences. Imbalance of activating and deactivating mechanisms including dysfunctions of ergo- and tropho-tropic over-segmentary centers was registered. Strengthening cortical connections in the right cortical hemisphere and their short circuit on temporal sections during geomagnetically disturbed days were observed, while, in geomagnetically quiet days, a profile of correlation interrelations reflected weak internal- and inter-hemispheric connections. The threshold of convulsive (spasmodic) readiness of the human brain is reduced, which is especially dangerous for risk group persons. It is established that, in general, weak and moderate geomagnetic storms exert stimulating influence while strong disturbances of geomagnetic conditions activate braking (inhibiting) processes.